ANALISA SISTEM INFORMASI UPLOAD PROMOSI HARGA MENGGUNAKAN SAP TERHADAP KEPUASAN PENGGUNA PADA PT HERO SUPERMARKET Tbk - Eka Wulansari Fridayanthie (Jurnal Khatulistiwa Informatika, 2016)
SAP is a system that investigated its impact on user satisfaction in PT Hero Supermarket Tbk. In this study tested the effect of system quality and quality of information on user satisfaction using the basic method of success DeLone and Mclean. This study uses a quantitative approach to mapping the characteristics of the data by means of descriptive statistics. The results showed that the Quality System (X1) and quality information (X2) influential either jointly towards user satisfaction (Y) Promotion of SAP. T significant value for the quality of the system is smaller than the specified α (α = 0.05), ie 0,000. In addition, the test results also show the value of t is greater than t table (4.533> 1.672) for the quality of the information system, Based on the test results it can be concluded that H0X1 be denied that the quality system (system quality) no positive effect on satisfaction user (user satisfaction) and HaX1 accepted for the quality of the system means that the quality of information systems (X1) has a positive and significant impact on user satisfaction of information systems. Significance for 0,000 t of quality information. And t is greater than t table (7.050> 1.672)., So H0X2 HaX2 rejected and accepted, meaning that the quality of information positively affects user satisfaction. Results of the study also concluded that the quality of information (X2) has a dominant influence on user satisfaction (Y).